Technological Solution of Biogas Output Increasing at Grain Distillery Spent Wash Fermentation - Nataliia Golub; Mariana Potapova (Innovative Biosystems and Bioengineering, 2018)
Background. Distillery spent wash is the main waste of the alcohol industry. This is highly concentrated wastewater, which is characterized by high chemical oxygen demand (COD) values – up to 60–120 g O2/dm3 – and low pH values – up to 3.7. It makes its processing a complicated task. One of the methods of its utilization is anaerobic fermentation with the production of biogas. Inert carriers for microorganism immobilization or granulation are used to intensify the process of anaerobic treatment and increase sludge concentration. Due to the high concentration of anaerobic microorganisms in granules, compared to the number of microorganisms in free-floating active sludge, the process of methanogenesis is more intensive with a high yield of biogas and a decrease in COD.